NILAI TAMBAH DAN KEHIDUPAN PETANI PADI SAWAH PADA IRIGASI UPPER KOMERING DI KABUPATEN OKU TIMUR - Imam Asngari; Ahmad Sudiro (Jurnal Ekonomi Pembangunan, 2010)
The purpose of study is to analysis of farmers performance in Ogan Komering Ulu Timur Municipality. Sampling method by stratified random sampling on 80 size farmers with the based on the land size. The location of the research are at Sidodadi and Sriwangi villages, in Belitang and Semendawai SUku III regency. The technique analysis by using qualitative and quantitative approach with the value added, efficiency and poverty level. Finding shows that value added at the Sriwangi more than Sidodadi  villages, but it’s the low of efficiency performance. Efficient Farmer’s is reached when value added and productivity highly, lower cost production, and labor exploitation. Factors inefficiency this causing lost of lower productivity, intensification, and optimum allocation input factors, such as labor, fertilization, and harvesting cost.  All of the impacted assumedly exploitation mechanism, to the impact on decreasing farmer’s efficient and it’s does to affecting leveling up in the poverty. The poverty increase with the stagnation, polarization of land and increasing of transformation peasant to hired farmer.  The farmers poor reach to 76,25 percent. In economic aspect, the poverty caused by self exploitation, lower productivity, and inefficient in the process of the production. Keyword: productivity, value added, efficiency, and poverty.